Desain dan Evaluasi Usabilitas Game Edukasi: Integrasi Laboratorium Virtual dan Petualangan untuk Pembelajaran Berpikir Komputasional - Yuda Okta Setia Perdana; Sukirman Sukirman (TIN: Terapan Informatika Nusantara, 2026)
Computational Thinking is an important competency that junior high school students must master, but the learning process is often hampered by the abstract nature of the material and the lack of engaging interactive media. As a result, students' learning motivation decreases, and they have difficulty understanding key stages such as decomposition, abstraction, and algorithm design. This study aims to develop and evaluate the usability of the educational game LEGEND AETHERIA, which is specifically designed as an interactive learning tool to support computational thinking skills for junior high school students. The method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. This game was built using Construct 3, integrating adventure mechanisms and virtual laboratory simulations. The adventure and virtual laboratory mechanisms are designed to help students practice stages of computational thinking, such as decomposition, abstraction, and algorithm design, through structured and contextual game-based activities. The evaluation was conducted through a limited trial involving 30 junior high school students, using the System Usability Scale (SUS) instrument to measure usability. The results showed an average SUS score of 85.25, which is classified as Very Good. These findings indicate that the LEGEND AETHERIA game has a very high level of ease of use and is well received by users. Thus, it can be concluded that the game developed can be used as an interactive learning medium for junior high school students.